The Influence Of Innovation And Product Quality On The Competitive Advantage Of Compass Products - Nazhifan Adilfi; Lia Yuldinawati (Eduvest - Journal of Universal Studies, 2024)
The fashion industry continues to experience rapid development, providing great business opportunities, especially in the shoe sector. The Compass company as one of the local shoe manufacturers in Indonesia faces intense competition, which requires them to continue to innovate and improve product quality in order to achieve competitive advantage. This study aims to determine the effect of innovation and product quality on the competitive advantage of Compass products. The research method used is quantitative method with descriptive-causality research type. Sampling was carried out using non-probability sampling technique saturated sampling type with 100 respondents. Data were analyzed using multiple linear regression analysis. The results showed that product innovation has a significant effect on competitive advantage with a t value of 5.512> t table 1.988, and product quality also has a significant effect on competitive advantage with a t value of 4.510> t table 1.988. Simultaneously, product innovation and product quality have an effect of 60.6% on competitive advantage, while 39.4% is influenced by other variables outside this study. The conclusion of this study is that product innovation and quality play an important role in creating a competitive advantage for Compass products.